Establishment of detailed loss functions for the urban flood risk assessment in Chao Phraya River basin, Thailand. Issue 1 (1st January 2019) - Komolafe, Akinola Adesuji; Herath, Srikantha; Avtar, Ram
Abstract: The continuous increase in damages to flood disasters globally has informed the need to assess vulnerability of built-up exposures for future flood risk reduction. The aim of this paper is to understand the contributions of some important variables in flood damage processes and develop loss functions for global building types, for the estimation of flood economic damages in Chao Phraya river basin, Thailand. We obtained empirical damage data (118 samples) through questionnaire survey in the study area for analysis. Using multiple linear regressions analysis, we generated loss functions for the aggregated residential building incorporating multiple damage factors. Further, disaggregated vulnerability curves (as a function of water depth) were established using logarithm function for three global building types in the study area. Results showed that, under flood condition in the study area, water depths and building age are very important damage factors, other variables are also emphasized. The loss models show maximum predicted vulnerability indices of 0.36, 0.30 and 0.10 for wooden, concrete frame and unreinforced masonry, and reinforced concrete moment frame, respectively. These functions can be used for modeling flood damage, for future disaster risk reduction and for risk comparison across countries.